NETIZEN DALAM KAMPANYE PILPRES RI 2014 - Madrah, Muna Yastuti; Mubarok, Mubarok (Master of Communication Science Program, Universitas Diponegoro, 2018)
The efforts to involve netizens in disseminating information about the candidates of president and vice president became a significant campaign strategy in the Indonesian’s president election 2014, especially for the beginners and middle-class voters. It is to confirm that the country with experienced a long period of authoritarianism tends to begin the political consciousness by rising awareness in which the community has turned into an active community and full of ideals. The middle class is the appropriate target for political campaign in social media, because of their highly movement in the cyber space. The other reason the new voter (beginners) are also targeted in the social media campaign during the Indonesia’s president election because their frequent access to social media. By using thick description of qualitative methods, the study illustrates how Indonesians netizens play a role in political communication strategy in social media during the campaign period. The future of Indonesia democracy should consider the role of netizens in order to develop ideal political communication strategy.